Microfinance - A Device to Empower Women (Global Journal of Management and Business Research, 2019)
Microfinance is emerging as a powerful tool in eradicating poverty in India. Microfinance has helped in the upliftment of the poor. Banks are not willing to provide credit assistance directly to the poor since they know that they will not be in a position to repay the loan, however the microfinance institutions have played a pivotal role in providing loans to the poor without any collateral. Microfinance has also helped in the upliftment of women in the society. Economic empowerment helps women by encouraging and enabling them to become entrepreneurs. The status of women in the society is improving and microfinance has helped to evoke confidence among women. Women empowerment helps in reducing the disparity between men and women on economic and social grounds. The present paper focuses on the role of microfinance institutions in empowering women in the society.
Keywords: empowerment; microfinance; microcredit; upliftment; etc